Steady global surface warming from 1973 to 2022 but increased warming rate after 1990 - B. H. Samset; C. Zhou; J. S. Fuglestvedt; M. T. Lund; J. Marotzke; M. D. Zelinka (Communications Earth & Environment, 2023)
Abstract The change in global mean surface temperature is a crucial and broadly used indicator of the evolution of climate change. Any decadal scale changes in warming rate are however obfuscated by internal variability. Here we show that the surface temperature increase through the recent La Nina influenced years (2022) is consistent with the 50-year trend of 0.18 °C/decade. We use an Earth System Model based tool to filter out modulations to the warming rate by sea-surface temperature patterns and find consistent warming rates in four major global temperature data series. However, we also find clear indications, in all observational series, of a step-up in warming rate since around 1990. CMIP6 models generally do not capture this observed combination of long-term warming rate and recent increase.